2009
DOI: 10.1007/s00592-009-0166-8
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic and antihyperlipidemic effects of Ziziphus vulgaris L. onreptozocin-induced diabetic adult male Wistar rats

Abstract: Herbal medicine and medical plants such as Ziziphus vulgaris L. are widely used for the treatment of diseases such as diabetes mellitus. We investigated the effects of water extracts of Ziziphus vulgaris L. fruit on serum glucose, triglycerides, LDL-cholesterol, HDL-cholesterol and activities of aminotransferase enzymes inreptozocin-induced diabetic adult male rats. Continuous supplementation of this water extract by gavage at doses of 0.25, 0.5, 1, 1.5 and 2 g/kg in 0.5 ml distilled water in diabetic rats res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Similar results have also been reported in rats that received hepatotoxic agents (Yossef et al , ). In a study on diabetic rats that were gavaged with extract of ZJF, TG levels decreased but the levels of LDL‐C and HDL‐C were not significantly changed after 14 days (Solati and Soleimani, , ). Water extract of ZJF indicated no significant change in HDL‐C level in diabetic rats (Solati and Soleimani, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have also been reported in rats that received hepatotoxic agents (Yossef et al , ). In a study on diabetic rats that were gavaged with extract of ZJF, TG levels decreased but the levels of LDL‐C and HDL‐C were not significantly changed after 14 days (Solati and Soleimani, , ). Water extract of ZJF indicated no significant change in HDL‐C level in diabetic rats (Solati and Soleimani, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the effects of this fruit on obesity and hyperlipidaemia (Sabzghabaee et al, 2013), liver disorders (Shen et al, 2009), hypertension (Koffi et al, 2008) and infectious disease. Antidiabetic and hypolipidaemic effects of Ziziphus have been illustrated in streptozocin-induced diabetic rats (Glombitza et al, 1994, Naftali et al, 2009, Solati and Soleimani, 2010a, 2010b, Hemmati et al, 2015. Avizeh et al (2010) demonstrated that administration of Ziziphus spina-christi extract for 10 days is associated with reduction in blood glucose level and increase in serum insulin, in diabetic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Ziziphus consists of about 100 species of deciduous or evergreen trees and shrubs throughout the world (Abalaka et al, 2010). Z. spinachristi has been among the key plants of the Iranian traditional medicine since ancient times and is indigenous and naturalized throughout Iran (Solati and Soleimani, 2010). It has been known as "Sedr" in Iran and wildly distributed in East, South, North-East and central parts of *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of this dose was based on previous studies which administered jujube extract at the same dose [14]. STZ in low dose is a β-cell toxin that has been commonly used for rapid and irreversible induction of type I diabetes [15].…”
Section: Experimental Designmentioning
confidence: 99%